The Phonological Influences on Non-Native Phonetic Change - Maryana Sitinjak; Rahmadsyah Rangkuti (Riviera Publishing, 2022)
Introduction: Studies of cross-language perception at the segmental level generally find that adults have great difficulty understanding the contrast of non-native consonants and/or vowels. Non-original phonotactics are often generated by type accuracy and error. Purpose: This article examines the effect of phonology on non-native phonetic changes. Methods: This research is a qualitative research with a literature review study method from the latest research. The collected data were analyzed by in-depth analysis. Results: Based on the results of data analysis, it shows that non-native speakers are not as accurate in the production of different illegal sequences. These findings also imply that linguistic experiences with native tones need not facilitate non-native phonetic changes. However, non-native phonetics change if there is habituation and construction in the right way. Conclusion: It can be concluded that non-native English still has problems in proper English articulation. Given the importance of phonetic accuracy in expressing spoken messages, foreign speakers must pay close attention to this matter and fix it by encouraging, involving and involving them every time to practice.